Light and Color in the Outdoors - Minnaert, Marcel. author. aut Link
XVII, 417 p.
Keywords: All of science springs from the observation of nature. In this classic book, the late Marcel Minnaert accompanies the reader on a tour of nature's light and color and reveals the myriad phenomena that may be observed outdoors with no more than a pair of sharp eyes and an enquiring mind. From the intriguing shape of the dapples beneath a tree on a sunny day, to rainbows, mirages, and haloes, to the colors of liquid, ice, and the sky, to the appearance of the sun, moon, planets, and stars - Minnaert describes and explains them all in clear language accessible to the layman. This volume includes 80 new photographs, over half in color, illustrating many of the phenomena - ordinary and exotic - discussed in the book. Most of the new photos are by Pekka Parviainen, the renowned Finnish nature photographer.